Rancang Bangun Bilah Berbahan Expanded Polystyrene (EPS) Foam untuk Kecepatan Angin Rendah pada Produk Horizontal Axial Wind Turbine - Setyaningrum, Rosmawan Arwinda; Corio, Dean (Program Studi Teknik Elektro Universitas Khairun, 2022)
The increasing use of electrical energy is inversely proportional to the diminishing fossil energy sources. New and Renewable EnergyÃ‚Â is one of the alternative energy that is being developed now. One of the energy used in the utilization of new and renewable energy is wind energy. In this study, we will discuss the manufacture of blades made from Expanded Polystyrene (EPS) Foam which is intended for wind turbines at low wind speeds. The use of this material is used and is able to form a blade with a weight of Ã‚Â± 300gram. This blade uses an Inverse Tapper type blade, which is a blade with an enlarged geometry at the tip, this geometry has a large surface so that it can receive more wind so that it can rotate at low wind speeds. The design and manufacture of blades is carried out using Aeolus ASP software which is open source on several analysis features and serves to determine the performance of the blades as well as to analyze aerodynamics and optimization of the shape of the blades designed to use Blade Element Momentum (BEM). This blade is capable of producing a voltage of 12.09 V. In the process of making the blade using wire cut to create geometry with National Advisory Committee for National Aeronautics (NACA) 4412 airfoil. The blade uses layers of balsa wood and monocote plastic sheets, and uses wood plywood as the base of the blade.